2009
DOI: 10.1021/jp8098768
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Electroluminescence from MgZnO-Based Heterojunction Light-Emitting Diodes

Abstract: We report on the fabrication of an n-Mg0.12Zn0.88O/p-GaN heterojunction light-emitting diode with an MgO dielectric interlayer by plasma-assisted molecular beam epitaxy. The current−voltage curve of the heterojunction diode showed obvious rectifying characteristics with a threshold voltage of about 8 V. Under forward bias, an ultraviolet electroluminescence (EL) emission located at about 374 nm coming from the Mg0.12Zn0.88O layer was observed at room temperature. This is one of the shortest EL emissions observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…As the injection current increases from 3.05 to 8.80 mA, all the spectra exhibit a strong emission at about 395 nm. Similar emission has been observed in our previous publication [17], and it has been attributed to the emission from ZnO with the MgO layer modulating the carrier transportation in the heterojunction [16,17]. The MgO layer will block the drift of electrons in the n-ZnO to the p-GaN for the large conduction band offset between ZnO and MgO (3.55 eV), while because the valence band offset between GaN and MgO is much smaller (0.9 eV), and the conduction and valence bands of MgO will bend significantly under forward bias, the effective thickness of the barrier that blocks the injection of holes from p-GaN to nZnO will be greatly reduced.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As the injection current increases from 3.05 to 8.80 mA, all the spectra exhibit a strong emission at about 395 nm. Similar emission has been observed in our previous publication [17], and it has been attributed to the emission from ZnO with the MgO layer modulating the carrier transportation in the heterojunction [16,17]. The MgO layer will block the drift of electrons in the n-ZnO to the p-GaN for the large conduction band offset between ZnO and MgO (3.55 eV), while because the valence band offset between GaN and MgO is much smaller (0.9 eV), and the conduction and valence bands of MgO will bend significantly under forward bias, the effective thickness of the barrier that blocks the injection of holes from p-GaN to nZnO will be greatly reduced.…”
Section: Resultssupporting
confidence: 87%
“…We have recently found that by modulating the carrier transportation process in n-ZnO/p-GaN heterojunction using a thin MgO dielectric layer, intense electroluminescence (EL) or even low-threshold lasing can be obtained [16,17]. In this paper, an n-ZnO/MgO/p-GaN heterojunction diode with MgO layer modulating the carrier transportation has been fabricated, and a phosphor blend was coated onto the heterojunction diode to form a phosphor-converted LED.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, ZnO has a wide band-gap of 3.37 eV and a large exciton binding energy of 60 meV. Many research results show that ZnO has a good excitonic emission performance at room temperature even at higher temperatures, so it is an ideal material for fabrication of short-wavelength emission devices such as ultraviolet lightemitting diodes [1,2]. So far, many ZnO nanostructures such as nanowires [3], nanobelts [4], nanorods [5], etc., have been prepared and widely investigated, but ZnO thin films are still the ZnO materials which have been studied most widely and deeply.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all the traditional light-emitting devices, including not only LD but also LED, rely on the non-excitonic origin of the light emission, eventually necessitating the sophisticated, expensive device-technologies. The only exception is the ZnO-based UV-LED recently achieved by Zhu et al experimentally [91]-its light emission is dominated by excitonic luminescence, owing to a large binding energy (60 meV [92]) and thus the stability (even at room temperature) of the ZnO excitons.…”
Section: Advantages and Possibility Of Using Metal Halides For Uv/ Vumentioning
confidence: 99%